A ribodepletion and tagging protocol to multiplex samples for RNA-seq based virus detection: application to the cassava virome - Daniel H. Otron; Justin S. Pita; Murielle Hoareau; Fidèle Tiendrébéogo; Jean-Michel Lett; Pierre Lefeuvre (Virology Journal)
Abstract Background Cassava (Manihot esculenta, Crantz), is a staple food and the main source of calories for many populations in Africa, but the plant is beset by several damaging viruses. So far, eight families of virus infecting cassava have been identified; the Geminiviridae (ssDNA viruses responsible for cassava mosaic disease, CMD) and Potyviridae (ssRNA + viruses responsible for cassava brown streak disease, CBSD) families being the most damaging to cassava in Africa. In several cassava-growing regions, the co-existence of species and strains from these two families results in a complex epidemiological situation making it difficult to correctly identify the viruses in circulation and delaying the implementation of disease management schemes. Nevertheless, the development of next generation sequencing (NGS) methods has revolutionized plant virus detection and identification. One NGS method that has been successfully used in virus detection and identification is ribodepleted RNA sequencing. Unfortunately, the relatively high cost makes it difficult to upscale this method to large epidemiological surveys and limits its adoption as a diagnostic tool. Results Here, we develop a high-throughput sequencing protocol, named Ribo-M-Seq, that combines plant rRNA ribodepletion, cDNA synthesis, tagging with a 96 multiplexing scheme and Illumina sequencing. We evaluated the protocol on a series of cassava samples with a known assemblage of viruses. After confirming that the protocol was suitable for ribodepletion, we demonstrated it was possible to detect RNA and DNA viruses via identification of near full-size genomes. Additional phylogenetic analyses confirmed the presence of begomoviruses and ipomoviruses responsible for CMD and CBSD, respectively. We also detected a recently described ampelovirus (Manihot esculenta-associated virus) that was not detected in previous analyses. Conclusions The use of the Ribo-M-Seq protocol will pave the way for large-scale sample analyses of collections with potentially complex viromes, such as those collected in the West African cassava integrated pest management program.